Does Medicaid Managed Care Help Equalize Racial and Ethnic Disparities in Utilization?. (12th October 2015) - Marton, James; Yelowitz, Aaron; Shores, Meredith; Talbert, Jeffery C.
Abstract : Objective: To estimate the impact of different forms of Medicaid managed care (MMC) delivery on racial and ethnic disparities in utilization. Data Source: Longitudinal, administrative data on 101, 649 children in Kentucky continuously enrolled in Medicaid between January 1997 and June 1999. Outcomes considered are monthly professional, outpatient, and inpatient utilization. Study Design: We apply an intent‐to‐treat, instrumental variables analysis using the staggered geographic implementation of MMC to create treatment and control groups of children. Principal Findings: The implementation of MMC reduced monthly professional visits by a smaller degree for non‐whites than whites (3.8 percentage points vs. 6.2 percentage points), thereby helping to equalize the initial racial/ethnic disparity in utilization. The Passport MMC program in the Louisville‐centered region statistically significantly reduced disparities for professional visits (closing the gap by 8.0 percentage points), while the Kentucky Health Select MMC program in the Lexington‐centered region did not. No substantive impact on disparities was found for either outpatient or inpatient utilization in either program. Conclusions: We find evidence that MMC has the possibility to reduce racial/ethnic disparities in professional utilization. More work is needed to determine which managed care program characteristics drive this result.